Cultural-Historical Approach to the System of Mass Education in Russia in the First Third of the XX Century: Ethnopsychological Aspect - Bozhovich, E.D. (Socialʹnaâ Psihologiâ i Obŝestvo, 2022)
Objectives. 1. To analyze the socio-political conditions in which pedagogical psychology as a sci¬entific discipline began to develop and the educational system in the USSR at the beginning of the XX century was formed. 2. To consider L.S. Vygotsky’s approach to the diagnosis of the mental develop¬ment of children of different nationalities for the subsequent pedagogically correct organization of their upbringing and educating. Background. The initial stages of the development of the education system in our multinational country and the formation of pedagogical psychology as an independent discipline are closely but am¬biguously linked. There is still an underestimation of both the achievements in solving the problems of education at that time, and misunderstanding of the role of psychologists in this work, in particular the research of L.S. Vygotsky, to whom disrespect for the culture of national minorities, colonization intentions, and a racist belief system are attributed in the foreign scientific press. Method. Analysis of the socio-political situation in the Russian education in the first third of the XX century. Comparative logical-semantic analysis of L.S. Vygotsky’s early works and his subsequent mature works, in which the main provisions of cultural-historical psychology were formulated. Conclusions. The significance of psychological research becomes more clearly expressed when ana¬lyzing and evaluating it not only in the scientific, but also in a broad social context. The role of L.S. Vygotsky in developing the approaches on the educational system in a multinational state is that he was actually the first to show the need to study the social situation of the development of children living in different ethnic environments. At the same time, he himself perceived national minorities as culturally peculiar, and not primitive, retarded. Цели. 1. Проанализировать социально-политические условия, в которых начала развиваться педагогическая психология как научная дисциплина и формироваться образовательная система в СССР в начале XX века. 2. Рассмотреть подход Л.С. Выготского к диагностике психического развития детей разной национальной принадлежности для последующей педагогически корректной организации их воспитания и обучения. Контекст и актуальность. Начальные этапы развития системы образования в нашей многонациональной стране и становление педагогической психологии как самостоятельной дисци¬плины тесно, но неоднозначно связаны. До сих пор имеет место недооценка как достижений в решении задач образования в тот период, так и непонимание роли психологов в этой работе, в частности исследований Л.С. Выготского, которому в зарубежной научной печати приписывается неуважение к культуре национальных меньшинств, колонизационные интенции, расистское мировоззрение. Метод. Анализ социально-политической ситуации в российском образовании в первой трети XX века. Сопоставительный логико-семантический анализ ранних работ Л.С. Выготского и его последующих, зрелых, трудов, в которых были сформулированы основные положения культурно-исторической психологии. Основные выводы. Значение психологического исследования получает более отчетливое выражение при анализе и оценке его не только в собственно научном, но и широком социальном контексте. Роль Л.С. Выготского в разработке подходов к построению образовательной системы в многонациональном государстве состоит в том, что он фактически первый показал необходимость изучения социальной ситуации развития детей, живущих в разных этнических средах. При этом сам он воспринимал национальные меньшинства как культурно-своеобразные, а не примитивные, отсталые.